The Use of Authentic Texts and Digital Media in Qirā’ah Instruction at Madrasah Aliyah: a Qualitative Study - Dadan Nugraha; Ilma Nurul Amalia; Syukron Kurniawan (UIN Sunan Gunung Djati Bandung, 2026)
Qirā’ah (reading) instruction at Madrasah Aliyah continues to face challenges, including the limited use of artificial or non-authentic learning materials and the low level of students’ exposure to linguistic contexts used by native speakers. Meanwhile, technological advancements offer opportunities to create more contextual learning through the integration of authentic texts and digital media. This study aims to describe the forms of authentic text utilization, patterns of digital media use, supporting and inhibiting factors in implementation, and their impact on students’ Qirā’ah abilities. The method used is a descriptive qualitative study based on library research, examining various literature on Arabic reading instruction, authentic texts, and digital media innovations. The findings indicate that authentic texts such as news articles, magazines, dialogues, and social media content provide natural language exposure and enhance discourse comprehension as well as vocabulary mastery. Digital media contribute by expanding access to learning resources, increasing interactivity, and optimizing reading strategies through multimedia features and online dictionaries. Supporting factors for implementation include teacher preparedness, availability of reading materials, student motivation, and adequate infrastructure. Conversely, challenges arise from text difficulty, dependence on digital translation, limited devices, and disparities in digital competence between teachers and students. Overall, the integration of authentic texts and digital media strengthens students’ motivation, reading strategies, and learning autonomy, thereby making a significant contribution to improving the quality of Qirā’ah instruction at Madrasah Aliyah.